Insight into IKBKG/NEMO Locus: Report of New Mutations and Complex Genomic Rearrangements Leading to Incontinentia Pigmenti Disease. Issue 2 (12th December 2013) - Conte, Matilde Immacolata; Pescatore, Alessandra; Paciolla, Mariateresa; Esposito, Elio; Miano, Maria Giuseppina; Lioi, Maria Brigida; McAleer, Maeve A.; Giardino, Giuliana; Pignata, Claudio; Irvine, Alan D.; Scheuerle, Angela E.; Royer, Ghislaine; et al.
<x xml:space="preserve">Abstract</x> Incontinentia pigmenti is a genomic disorder caused by mutation in IKBKG/NEMO X‐linked gene. Here, we present 21 point mutations previously unreported and a new microindel (c.436_471delinsT, p.Val146X) arising through a DNA‐replication‐repair fork‐stalling‐and‐template‐switching and microhomology‐mediated‐end‐joining mechanism in a sporadic IP case. A locus specific database, accessible at http://IKBKG.lovd.nl, will give a complete overview of all the variants identified and secure the appropriate use of genotype and phenotype information of patients. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>